1997
DOI: 10.1111/0023-8333.101997010
|View full text |Cite
|
Sign up to set email alerts
|

The Modification of Onsets in a Markedness Relationship: Testing the Interlanguage Structural Conformity Hypothesis

Abstract: The Interlanguage Structural Conformity Hypothesis (Eckman, 1991) predicts that implicational universals influence the structuring of interlanguage phonology. Under one interpretation, L2 learners will modify more marked structures more frequently than less marked structures. This study tested that hypothesis by examining how frequently 11 young adult, native Spanish speakers modified English 2-and 3-member onsets, the latter being more marked than the former. The environments before the onsets and the sonorit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
27
0
2

Year Published

1999
1999
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 15 publications
3
27
0
2
Order By: Relevance
“…The study confirmed most of the results from previous research, for example, that the frequency of epenthesis varies with preceding phonetic environment. However, the study suggested that a lowering effect of preceding vowels must be present, not just the enhancing effect of preceding consonants suggested by Carlisle (1997). …”
mentioning
confidence: 78%
See 3 more Smart Citations
“…The study confirmed most of the results from previous research, for example, that the frequency of epenthesis varies with preceding phonetic environment. However, the study suggested that a lowering effect of preceding vowels must be present, not just the enhancing effect of preceding consonants suggested by Carlisle (1997). …”
mentioning
confidence: 78%
“…As the reader will note, Robert Carlisle alone is responsible for the vast majority of empirical studies available today on the epenthesis of /sC(C)/ onsets in the L2 production of L1 Spanish speakers (see Carlisle, 1988Carlisle, , 1991aCarlisle, , 1991bCarlisle, , 1992Carlisle, , 1994Carlisle, , 1997Carlisle, , 1998. Even though Carlisle's theoretical approach was outlined and explained in some detail in several articles (e.g., 1991a, 1997), and even though it is beyond the scope of this article to evaluate how well different phonological theories account for the Spanish #esC(C) pattern or the L2 production of Spanish learners, it is still worthwhile to iterate Carlisle's approach here, and also to present an opposite view.…”
Section: Two Opposing Views On the Spanish #Esc(c) Pattern And Their mentioning
confidence: 99%
See 2 more Smart Citations
“…Outra seqüência problemática do inglês, objeto de pesquisas recentes com falantes nativos de espanhol e português, são os encontros consonantais iniciais com /s/: /sp, st, sk, spr, spl, str, skr, skw, sm, sn, sl/ (CARLISLE, 1992(CARLISLE, , 1994(CARLISLE, , 1997(CARLISLE, , 1998REBELLO, 1997, RAUBER, 2002. Embora nenhuma dessas pesquisas lidou com percepção, há evidências do ensino da pronúncia do inglês para alunos intermediários brasileiros: vários alunos meus apresentaram grandes dificuldades em exercícios de distinção entre pares como specially/especially e state/estate.…”
unclassified